Question
Wed August 29, 2012 By:

2(sin^6 A+cos^6 A)-3(sin^4 A+cos^4 A)+1=0

Expert Reply
Wed August 29, 2012

SIN6 A + COS 6A IS IN FORM OF A+ B3

SIN6A+ COS 6 A = ( SIN A + COS 2A ) 3 - 3 SIN2A * COS2A ( SIN 2A + COS 2A )

=> 13 - 3 SIN2A * COS2A

ALSO SIN4A + COS 4A IS IN FORM OF A+ B2

SIN4A + COS 4A = ( SIN 2A + COS 2A)- 2 ( SIN 2A * COS 2A)

=> 1 2 - 2 ( SIN 2A * COS 2A)

Now, LHS = 2(sin6A + cos6A) - 3(sin4 + cos4) +1 =

(13 - 3 SIN2A * COS2A ) - 3 ( 1 2 - 2 SIN 2A * COS 2A) + 1

= 2 - 6 SIN 2A * COS 2A - 3 + 6 SIN 2A * COS 2A + 1

= 0

Related Questions
Ask the Expert